1985
DOI: 10.1002/jsfa.2740361208
|View full text |Cite
|
Sign up to set email alerts
|

A chemical study of Balanites aegyptiaca L. (Lalob) fruits grown in Sudan

Abstract: Two samples of Balanites aegyptiaca fruits were collected from two different regions in Sudan, The edible mesocarp contained 1.2-1.5% protein and 3537% total sugars of which 81.3-91.1% is present as reducing sugars. The kernels contained 45.0-46.1% oil. Palmitic, stearic, oleic and linoleic acids were the main fatty acids. The ratio of saturated to unsaturated fatty acids was 10:26 in both samples. The protein was found to be low in aromatic amino acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 4 publications
2
16
1
3
Order By: Relevance
“…Compared to the oil extracted from the raw sample, the fatty acid composition of the oil extracted from the processed samples remained roughly unchanged. The present results of the fatty acid composition of Balanites aegyptiaca oil are in good agreement with previous studies (Al Ashaal, et al 2010;Chapagain, 2009;Hussain, et al 1949;Mohamed, et al 2002;Nour et al1985) regarding the major fatty acids in the oil, however, except for Nour et al (1985), significant variations in the percentages of these acids could be noticed. The noticeable variations in the percentages of fatty acids were clarified by Chapagain et al (2009) who analyzed the fatty acid composition of six Balanites aegyptiaca genotypes.…”
Section: The Chemical Properties Of the Oilssupporting
confidence: 93%
See 3 more Smart Citations
“…Compared to the oil extracted from the raw sample, the fatty acid composition of the oil extracted from the processed samples remained roughly unchanged. The present results of the fatty acid composition of Balanites aegyptiaca oil are in good agreement with previous studies (Al Ashaal, et al 2010;Chapagain, 2009;Hussain, et al 1949;Mohamed, et al 2002;Nour et al1985) regarding the major fatty acids in the oil, however, except for Nour et al (1985), significant variations in the percentages of these acids could be noticed. The noticeable variations in the percentages of fatty acids were clarified by Chapagain et al (2009) who analyzed the fatty acid composition of six Balanites aegyptiaca genotypes.…”
Section: The Chemical Properties Of the Oilssupporting
confidence: 93%
“…As can be seen from the table, with the exception of peroxide value, the chemical properties of the oil extracted from the raw kernels compare well with the previous studies (Hussain, et al 1949;Nour et al 1985;Manji et al 2013). Nour et al (1985) have analyzed the oils of two different samples of Balanites aegyptiaca seeds originating from Sudan. They have found that the saponification values were 190.05 and 176.97, peroxide values 3.7 and 2.7, and acid values 0.40 and 0.50, respectively.…”
Section: The Chemical Properties Of the Oilssupporting
confidence: 88%
See 2 more Smart Citations
“…This caloric intake was lower than the value of 300 kcal 100 g -1 of pulp stated by Nour et al (1985) in Sudan fruits. It should be noted that the fruit pulp of B. aegyptiaca has a caloric intake greater than that of several tropical fruits, for example: banana (89 kcal), durian (126 kcal) and avocado (139 kcal) (Danthu et al, 2002).…”
Section: Energy Value Of Pulpcontrasting
confidence: 61%